2011
DOI: 10.1523/jneurosci.2801-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bmal1in the Nervous System Is Essential for Normal Adaptation of Circadian Locomotor Activity and Food Intake to Periodic Feeding

Abstract: Temporal restriction of feeding can entrain circadian behavioral and physiological rhythms in mammals. These changes in biological rhythms are postulated to be brought about by a putative food-entrainable oscillator (FEO) that is independent of the suprachiasmatic nucleus (SCN). However, the anatomical substrates and molecular machinery of FEO remain elusive. We report here that mice with a nervous system-specific deletion of Bmal1, an essential clock component, had a marked deficit in entrainment of locomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 24 publications
(34 reference statements)
4
50
0
Order By: Relevance
“…These mice do not display gross peripheral pathologies. Similar mice were previously reported to have partially intact Bmal1 expression in the SCN, rescuing the circadian regulation of locomotor activity and sleep (32). Locomotor circadian rhythms were largely retained in our NestinCre + ;Bmal1 f/f mice as compared with mice lacking Cre, with no genotype difference in the free-running period, although there was a trend toward a slightly shorter free-running period, similar to that reported previously (ref.…”
Section: Oscillation Of Circadian Clock Genes Is Controlled By Bmal1 supporting
confidence: 89%
See 1 more Smart Citation
“…These mice do not display gross peripheral pathologies. Similar mice were previously reported to have partially intact Bmal1 expression in the SCN, rescuing the circadian regulation of locomotor activity and sleep (32). Locomotor circadian rhythms were largely retained in our NestinCre + ;Bmal1 f/f mice as compared with mice lacking Cre, with no genotype difference in the free-running period, although there was a trend toward a slightly shorter free-running period, similar to that reported previously (ref.…”
Section: Oscillation Of Circadian Clock Genes Is Controlled By Bmal1 supporting
confidence: 89%
“…Locomotor circadian rhythms were largely retained in our NestinCre + ;Bmal1 f/f mice as compared with mice lacking Cre, with no genotype difference in the free-running period, although there was a trend toward a slightly shorter free-running period, similar to that reported previously (ref. 32, Figure 3, A-C, and Supplemental Figure 4A). Using EEG, we saw that grossly normal sleep-wake oscillation was retained in NestinCre + ; Bmal1 f/f mice in 12-hour light/12-hour dark housing conditions (Supplemental Figure 4, B and C).…”
Section: Oscillation Of Circadian Clock Genes Is Controlled By Bmal1 mentioning
confidence: 95%
“…It is particularly noteworthy that the product of Arntl ( Bmal1 ) is a transcription factor that is a core component of the mammalian circadian rhythm system (Buhr and Takahashi 2013). Studies with knockout mice indicate that Bmal1 plays an important role in the entrainment of locomotor activity that occurs when animals are put on a restricted feeding schedule (Mieda and Sakurai 2011; Zhang et al 2012). The DID paradigm is reminiscent of the restricted feeding protocol, in that alcohol is available only during a restricted period.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bmal1 expression was lower in brains of the LXS mice that showed higher alcohol consumption in the DID model (Table 3). The lower Bmal1 expression would be expected to result in lower locomotor activity in these mice during the period of restricted access to alcohol (Mieda and Sakurai 2011). Since our candidate gene results are based on whole brain transcriptional analyses, it is important to note that Bmal1 expression in regions of the brain outside of the suprachiasmatic nucleus were implicated in the adaptation to food restriction (Mieda and Sakurai 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Per2 mutant/ knockout mice and Bmal1-knockout mice were reported to exhibit normal FAA or reduced FAA in different studies performed in different laboratories (118 -121). Recently, Mieda and Sakurai (122) showed that nervous system-specific Bmal1 deletion caused a reduction in the entrainment ability of the scheduled-feeding paradigm, suggesting that Bmal1 is an essential component of the FEO. Additionally, Takasu et al (123) demonstrated that clock-gene mutant or knockout mice have different abilities for adapting to different periodic feeding paradigms (T-cycle experiment).…”
Section: Food Anticipatory Activity (Faa)mentioning
confidence: 99%